Du féminisme à la sexologie : un parcours en Histoire - Sylvie Chaperon (Genre, Sexualité et Société)
Throughout my time spent as a historian in research, and in French Universities, I’ve attempted to identify each generation that has studied feminism and gender, and the historical turns those groups have taken. I myself belong to the third feminist and gender studies generation; the first gathers the pioneers of the field, the second constitutes itself from students of the 1970’s, and the fourth is in its doctoral phase. Each one has evolved in specific institutional and scientific landscapes but all have had to face academic reticence. The object and purpose of my research is inscribed in the transition from the history of women and that of gender studies, and in the increase of the historical research done on sexualities.